Commonly Employed African Neonatal Skin Care Products Compromise Epidermal Function in Mice. Issue 5 (11th July 2016) - Man, Mao‐Qiang; Sun, Richard; Man, George; Lee, Dale; Hill, Zelee; Elias, Peter M.
Abstract: Background: Neonatal mortality is much higher in the developing world than in developed countries. Infections are a major cause of neonatal death, particularly in preterm infants, in whom defective epidermal permeability barrier function facilitates transcutaneous pathogen invasion. The objective was to determine whether neonatal skin care products commonly used in Africa benefit or compromise epidermal functions in murine skin. Methods: After twice‐daily treatment of 6‐ to 8‐week‐old hairless mice with each skin care product for 3 days, epidermal permeability barrier function, skin surface pH, stratum corneum hydration, and barrier recovery were measured using a multiprobe adapter system physiology monitor. For products showing some benefits in these initial tests, the epidermal permeability barrier homeostasis was assessed 1 and 5 hours after a single application to acutely disrupted skin. Results: All of the skin care products compromised basal permeability barrier function and barrier repair kinetics. Moreover, after 3 days of treatment, most of the products also reduced stratum corneum hydration while elevating skin surface pH to abnormal levels. Conclusion: Some neonatal skin care products that are widely used in Africa perturb important epidermal functions, including permeability barrier homeostasis in mice. Should these products have similar effects on newborn human skin, they could cause a defective epidermal permeability barrier, which can increase body fluid loss, impair thermoregulation, and contribute to the high rates of neonatal morbidity and mortality seen in Africa. Accordingly, alternative products that enhance permeability barrier function should be identified, particularly for use in preterm infants.